Akibat Hukum Tidak Melekatkan Sidik Jari dalam Minuta Akta Notaris terhadap Kekuatan Pembuktian Akta - Anak Agung Ngurah Danan Kusuma Wardana; Kadek Sarna; I Gusti Ngurah Dharma Laksana (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
This study aims to analyze the legal consequences of failing to attach fingerprints to the notarial deed protocol (minuta akta) on the evidentiary strength of the deed and to examine the regulation of such obligation under Law Number 2 of 2014 concerning the Position of Notary. This research employs a normative legal research method using statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary legal sources analyzed qualitatively through library research. The results indicate that the obligation to attach fingerprints to the notarial deed protocol constitutes one of the formal obligations of a notary intended to strengthen the identification of the parties and ensure legal certainty in the making of authentic deeds as stipulated in Article 16 paragraph (1) letter c of the Notary Position Law. However, the provision does not explicitly regulate the procedures for implementation nor the legal consequences if such obligation is not fulfilled, thereby creating a legal vacuum. The absence of fingerprints in the notarial deed protocol does not eliminate the authenticity status of the deed since the essential elements required for the formation of an authentic deed remain fulfilled. Nevertheless, the violation of such obligation affects the weakening of the evidentiary power of the deed, particularly in proving the identity and presence of the parties before the notary, thereby potentially causing disputes in judicial practice.